Peran Reward dan Punishment dalam Meningkatkan Minat Belajar Al-Qur’an Hadits di Madrasah Ibtidaiyah: Rewards, Punishments, Al-Qur’an Hadith - Andryadi; Rohana, Siti; Karsum; Saputriyani, Eka (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2025)
The study of Al-Qur’an Hadith is essential in developing students' foundational knowledge of religion and nurturing their moral values from an early stage. However, low motivation among Madrasah Ibtidaiyah (MI) students in engaging with this subject remains a significant challenge for educators. This study aims to theoretically examine the effectiveness of the reward and punishment method in enhancing students' learning motivation in Al-Qur’an Hadith lessons. Using a qualitative approach through library research, data were collected from academic journals, educational books, and relevant research findings. The results indicate that rewards such as verbal praise, symbolic awards, and positive reinforcement significantly increase student enthusiasm and engagement. On the other hand, mild punishments like warnings or reminders help develop discipline without reducing intrinsic motivation. This study highlights that a balanced implementation of rewards and punishments can serve as an effective pedagogical strategy to improve student participation in Al-Qur’an Hadith learning. Future studies are encouraged to integrate parental involvement and interactive learning methods to further enhance educational outcomes.